Comprehending the dynamism of B chromosomes in their journey towards becoming unselfish - Rajpal, Vijay Rani; Sharma, Suman; Sehgal, Deepmala; Sharma, Prashansa; Wadhwa, Nikita; Dhakate, Priyanka; Chandra, Atika; Thakur, Rakesh Kr.; Deb, Sohini; Rama Rao, Satyawada; Mir, Bilal Ahmad; Raina, Soom Nath (Frontiers in Cell and Developmental Biology, 2023)
Investigated for more than a century now, B chromosomes (Bs) research has come a long way from Bs being considered parasitic or neutral to becoming unselfish and bringing benefits to their hosts. B chromosomes exist as accessory chromosomes along with the standard A chromosomes (As) across eukaryotic taxa. Represented singly or in multiple copies, B chromosomes are largely heterochromatic but also contain euchromatic and organellar segments. Although B chromosomes are derived entities, they follow their species-specific evolutionary pattern. B chromosomes fail to pair with the standard chromosomes during meiosis and vary in their number, size, composition and structure across taxa and ensure their successful transmission through non-mendelian mechanisms like mitotic, pre-meiotic, meiotic or post-meiotic drives, unique non-disjunction, self-pairing or even imparting benefits to the host when they lack drive. B chromosomes have been associated with cellular processes like sex determination, pathogenicity, resistance to pathogens, phenotypic effects, and differential gene expression. With the advancements in B-omics research, novel insights have been gleaned on their functions, some of which have been associated with the regulation of gene expression of A chromosomes through increased expression of miRNAs or differential expression of transposable elements located on them. The next-generation sequencing and emerging technologies will further likely unravel the cellular, molecular and functional behaviour of these enigmatic entities. Amidst the extensive fluidity shown by B chromosomes in their structural and functional attributes, we perceive that the existence and survival of B chromosomes in the populations most likely seem to be a trade-off between the drive efficiency and adaptive significance versus their adverse effects on reproduction.